Heat Transfer Efficiency of Different Composite Insulators - Muhson Naji, Amel; M. Al-Shuwaiki, Najah; H. Abdulsalam, Ezzet (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
This research aims to investigate the thermal performance of different thermal composite insulators, wrapped around a closed-loop copper pipe (CLP). To achieve this aim a system was designed and manufactured. It is consisted of closed water tank insulated by Rock Wool, and supplied with two electric heaters, two thermostat, a flow meter, a water pump, digital temperature scales, and four series of (CLP).Six insulators were prepared namely; composites of Impregnated Fiberglass with Elastoclad and foaming Rubber (FER), Impregnated Fiberglass with Elastoclad resin and Polymeric Membrane (FEM), Impregnated Fiberglass with Polyurethane thermoset resin and Foaming Rubber (FUR), Impregnated Fiberglass with Polyurethane thermoset resin and Polymeric Membrane (FUM), Fiberglass woven tape (F) , and foaming rubber tape (R). Thermal conductivities of all composite specimens were measured by Lee's Disc device and their thermal performances were evaluated by measuring inlet and outlet temperature ΔTw at different flow rates. It was found from all test results that ΔTw decreased as flow rate increased.The optimum result was obtained for the (FER) insulator at flow rate 8 L/min where ΔTw = 0.8 oC (efficiency η = 99 %).Thermal efficiency of the prepared insulators was according to the following sequence:FER > FEM > FUR > FUM >R > F